THE EFFECTS OF PARASITIC RESISTANCES ON ORGANIC SOLAR CELL’S PERFORMANCE (Sciences & Technology. A, exactes sciences, 2007)
This publication aims to present a study of the current–voltage characteristics of organic solar cell based on a composite of poly (2-methoxy-5-(2’-ethylhexyloxy)-1, 4-phenylenevinylene (MEH-PPV) with [6, 6]-phenyl C60 butyric acid methyl ester (PCBM) as a function of illumination intensity. The variation of the photocurrent, the fill factor, the open-circuit voltage, the saturation current and the maximum output power under different light intensity values (100 mW/cm2, 60 mW/cm2 and 24 mW/cm2), were investigated experimentally. It is observed that for given values of series and/or shunt resistance, the fill factor is determined by reverse saturation current and diode quality factor of the solar cell.The effects of these components on the overall photovoltaic performance are discussed.